A head-driven treatment of asymmetric coordination and apposition - Van Eynde, Frank (Proceedings of the 12th International Conference on Head-Driven Phrase Structure Grammar, 2005)
In Pollard & Sag (1994) and in Ginzburg & Sag (2000) phrases are either headed or non-headed, and if they areheaded, there is a relation of selection between the daughters: either the head daughter selectsits non-head sister(s), as in the phrases of type ˋhead-complements', or the non-head daughter selects its headsister, as in the phrases of type ˋhead-adjunct'. In the non-headed phrases, by contrast, there is noselection; in a coordinate structure, for instance, there is no relation ofselection, neither between the conjuncts nor between the conjunction and the conjuncts. The central claim of this paper is that thereare also phrases which are headed but in which neither daughterselects the other. To model such phrases I propose a new type, calledˋhead-independent'. Its properties are spelled out and its rangeof application is illustrated with various examples, including asymmetric coordination and apposition.